Otto neurath and the unity of science - Symons, John; Pombo, Olga; Torres, Juan Manuel, 1947- (Logic, Epistemology, and the unity of science, 2011)
This volume critically reexamines Otto Neurath?s conception of the unity of science. Some of the leading scholars of Neurath?s work, along with many prominent philosophers of science critically examine his place in the history of philosophy of science and evaluate the relevance of his work for contemporary debates concerning the unity of science.